Impact of Dendrimers on Solubility of Hydrophobic Drug Molecules - Choudhary, Sonam; Gupta, Lokesh; Rani, Sarita; Dave, Kaushalkumar; Gupta, Umesh (Frontiers in Pharmacology, 2017)
Adequate aqueous solubility has been one of the desired properties while selecting drug molecules and other bio-actives for product development. Often solubility of a drug determines its pharmaceutical and therapeutic performance. Majority of newly synthesized drug molecules fail or are rejected during the early phases of drug discovery and development due to their limited solubility. Sufficient permeability, aqueous solubility and physicochemical stability of the drug are important for achieving adequate bioavailability and therapeutic outcome. A number of different approaches including co-solvency, micellar solubilization, micronization, pH adjustment, chemical modification, and solid dispersion have been explored towards improving the solubility of various poorly aqueous-soluble drugs. Dendrimers, a new class of polymers, possess great potential for drug solubility improvement, by virtue of their unique properties. These hyper-branched, mono-dispersed molecules have the distinct ability to bind the drug molecules on periphery as well as to encapsulate these molecules within the dendritic structure. There are numerous reported studies which have successfully used dendrimers to enhance the solubilization of poorly soluble drugs. These promising outcomes have encouraged the researchers to design, synthesize, and evaluate various dendritic polymers for their use in drug delivery and product development. This review will discuss the aspects and role of dendrimers in the solubility enhancement of poorly soluble drugs. The review will also highlight the important and relevant properties of dendrimers which contribute toward drug solubilization.